-2(7x-7)+7=-14x+21

Simple and best practice solution for -2(7x-7)+7=-14x+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7x-7)+7=-14x+21 equation:


Simplifying
-2(7x + -7) + 7 = -14x + 21

Reorder the terms:
-2(-7 + 7x) + 7 = -14x + 21
(-7 * -2 + 7x * -2) + 7 = -14x + 21
(14 + -14x) + 7 = -14x + 21

Reorder the terms:
14 + 7 + -14x = -14x + 21

Combine like terms: 14 + 7 = 21
21 + -14x = -14x + 21

Reorder the terms:
21 + -14x = 21 + -14x

Add '-21' to each side of the equation.
21 + -21 + -14x = 21 + -21 + -14x

Combine like terms: 21 + -21 = 0
0 + -14x = 21 + -21 + -14x
-14x = 21 + -21 + -14x

Combine like terms: 21 + -21 = 0
-14x = 0 + -14x
-14x = -14x

Add '14x' to each side of the equation.
-14x + 14x = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| n/3+5x75 | | 16/(x^2+6x+9)+(3)/(x+3) | | -148=1.8c+32 | | 10m^2+8=24m | | n/3+5 | | 2y^2-2y=24 | | 3z+7=25 | | -7(x-y)=-7(6) | | -38=8+6(y-2) | | X^2-16=8x | | -1(-7x+7y)=-1(-42) | | 4c+3c-2c= | | 5x+10=-4-17 | | 2x+6=204 | | 6x^2=13x-5 | | x(0)-2y=4 | | 4h+7i/5=2h-10j/-3 | | sec^2-tan^2+1= | | -1(12x-6y)=-1(6) | | 3y+4y+6= | | -6(-2x+y)=-6(2) | | 40-2x=8-8x | | (5/8)a=160 | | 2x+10=1x | | Y^4+10y^2+9=0 | | (-7m^3n^7)(2mn^2)= | | 748=550(1+0.18t) | | 6[-6+6+4(x+1)]=6x+6 | | 3(2z-5)=4z+2 | | cosx(tanx+cotx)= | | -6(2x+9)= | | -4-3x=-5(3x+4) |

Equations solver categories